(untitled) (Revista Lusófona de Educação, 2025)
Students with disabilities face unique challenges that affect their academic experience and effective integration into the university. There is a need to know how this issue has been addressed by researchers and what gaps need to be addressed. The objective was to analyze the scientific production about students with dis abilities in the university context. A bibliometric analysis was conducted, oriented toward the description of met rics and the understanding of the conceptual structure of the topic. A total of 509 documents retrieved from the Web of Science were analyzed. The results showed a predominance of research articles and group authorship. The authors and sources with the highest production were identified, which is useful for researchers. A thematic evolution from a disability-centered approach to one based on the individual was observed. The scientometric view made it possible to identify thematic trends and gaps for future research that contribute to achieving in clusive and equitable education. Among these topics are the evaluation and approach to the effectiveness of inclusion policies from the perspectives of students, families and teachers. It is concluded that it is pertinent to develop studies based on their centrality in the scientific community. Keywords: inclusive education; university education; disability; students.